Collagen Restoration from Combined Radiofrequency Microneedling and Polydioxanone Filler in Oxidative Stress-Mediated Skin Aging - Sinaga, Ruth Agustina; Paskaria, Cindra; Widowati, Wahyu (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Oxidative stress plays a central role in skin aging by promoting reactive oxygen species–mediated collagen degradation, fibroblast senescence, and dermal thinning. Although radiofrequency microneedling (RFM) and polydioxanone (PDO) filler individually stimulate collagen remodeling, evidence regarding their combined efficacy in oxidative stress induced skin aging models remains limited. This study evaluated the effects of combined RFM and PDO filler therapy in a D-galactose–induced oxidative stress model of skin aging.METHODS: Thirty female Sprague-Dawley rats were randomly assigned into five groups (n=5): normal control (NC), aging control (AC), RFM monotherapy, PDO monotherapy, and combination therapy. Oxidative aging was induced by daily intraperitoneal injections of 50 mg/kg for 8 weeks, followed by a single post-induction treatment session. Skin samples were collected at 12 weeks post-treatment for histological assessment of dermal thickness (hematoxylin–eosin), collagen density (Masson’s trichrome), and fibroblast count.RESULTS: D-galactose significantly reduced dermal thickness, collagen density, and fibroblast count in AC compared with NC (p<0.001). All treatment groups showed significant improvement versus AC (p<0.05). Notably, only the combination therapy restored collagen density to a level comparable with normal skin (35.22 [28.74–40.35]% vs. 37.83 [33.11–40.69]%, p=0.124). The combination group also showed the highest increases in dermal thickness and fibroblast numbers among treatment groups.CONCLUSION: In this preclinical model, combined RFM and PDO filler therapy demonstrated enhanced restoration of dermal structure and collagen under oxidative stress–mediated skin aging, supporting its potential role in skin rejuvenation strategies.KEYWORDS: collagen density, dermal regeneration, D-galactose, oxidative stress, skin aging